Characterisation and corrosion evaluation of sol gel alumina-gnp coating on nickel substrate - Aliaa, Zanurin (2023)
Alumina (Al2O3) is one of the most significant ceramic materials that is well known of its outstanding mechanical and thermal properties and useful for industrial purposes, especially as ceramic coating. Alumina coating served as a protection against corrosion by preventing the underneath layer from interacting with corrosive environment. Nickel is usually known for having high corrosion resistance towards caustic solution which is also where the usage of nickel is commonly found. However, nickel can corrode in an unusual way that jeopardise its function especially in the presence of chloride ion. Even when shielded by passive layers, nickel surfaces are still prone to localised corrosion. Therefore, the alumina coatings can be incorporated with graphene to improve the ceramic matrix to provide further protection against corrosion. This study aims to synthesise alumina-graphene nanoplatelets (Al2O3-GNPs) produced by sol gel method, to investigate the influence of the concentration of alumina and heat treatment on the coating and to evaluate the corrosion behaviour of the Al2O3-GNPs sol gel coated nickel substrate. The synthesis of Al2O3-GNPs has been successfully carried out to study the effect of different concentration of alumina and heat treatment on the corrosion behaviour on the coating. To characterise the coating, field emission-scanning electron microscope (FESEM), SEM, X-ray diffraction (XRD) and thermogravimetric (TG) tests were used. The corrosion behaviour of the coated samples is studied using electrochemical impedance spectroscopy (EIS) and potentiodynamic polarisation (PDP). The analysis through FESEM, showed that the nanoparticles appeared at some part on the surface of the coating due to the effect of concentration of alumina which can be seen from the porosity and agglomeration causes by the abruption of the viscosity of sol gel on the surface of the coating. Taking that into account, the presence of graphene can be interpreted in terms of its capability to catalyse the curing reaction and its role as a thermal stabiliser. The Nyquist plot from EIS revealed the half semi-circle curve for all samples. This kind of curve indicating the active charge transfer between the coating and the sodium chloride (NaCl) solution. The highest charge transfer resistance of Al2O3-GNPs coating at concentration of 0.01M at 900 C as a consequence of minor agglomeration and segregation of nanoparticles on the coating surface. The PDP analysis found that the concentration of alumina-GNPs at 0.1 M with heat treatment temperature of 900 C exhibited the lowest corrosion rate at 4.31 x 10-7 mm/year and the sample indicated a brief passivation behaviour. Thus, the incorporation of graphene with alumina ceramic coating using sol gel technique increases the corrosion resistance on the nickel substrate. Considering the potential of Al2O3-GNPs, it is possible to apply this coating on various application in the engineering industry specifically in manufacturing and electronics where the nickel is widely used.